2012
DOI: 10.1371/journal.pgen.1003121
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Signaling between the Ectoderm and a Mesendodermal Left-Right Organizer Directs Left-Right Determination in the Sea Urchin Embryo

Abstract: During echinoderm development, expression of nodal on the right side plays a crucial role in positioning of the rudiment on the left side, but the mechanisms that restrict nodal expression to the right side are not known. Here we show that establishment of left-right asymmetry in the sea urchin embryo relies on reciprocal signaling between the ectoderm and a left-right organizer located in the endomesoderm. FGF/ERK and BMP2/4 signaling are required to initiate nodal expression in this organizer, while Delta/No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
108
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 107 publications
11
108
1
1
Order By: Relevance
“…If this were the case, this polarization would inevitably result in a leftward fluid flow. Molecular data support our reasoning: manipulation of Notch signaling or of the ion pump ATP4 affects asymmetric Nodal expression in the sea urchin archenteron (Bessodes et al, 2012). A role of Notch in vertebrate LR axis determination has long been known (Krebs et al, 2003;Przemeck et al, 2003).…”
Section: Insights From Echinodermssupporting
confidence: 70%
“…If this were the case, this polarization would inevitably result in a leftward fluid flow. Molecular data support our reasoning: manipulation of Notch signaling or of the ion pump ATP4 affects asymmetric Nodal expression in the sea urchin archenteron (Bessodes et al, 2012). A role of Notch in vertebrate LR axis determination has long been known (Krebs et al, 2003;Przemeck et al, 2003).…”
Section: Insights From Echinodermssupporting
confidence: 70%
“…In addition, after gastrulation, nodal expression occurs in different germ layers depending on the group considered: the ectoderm in snails (Grande and Patel 2009), the ectoderm and endoderm in echinoderms (Duboc et al, 2010;Ohguro et al, 2011;Bessodes et al, 2012), all three germ layers in cephalochordates, urochordates, and hemichordates, and the endomesoderm in vertebrates (Hamada et al, 2002;Morokuma et al, 2002;Yu et al, 2002;Duboc et al, 2005;Wlizla 2011). Here we have shown that in brachiopods nodal is restricted to the mesoderm.…”
Section: Tracing the Origin Of The Nodal Pathwaymentioning
confidence: 99%
“…However, unlike vertebrate nodal, which is expressed in the endomesoderm and is involved in its induction, non-vertebrate deuterostome nodal is expressed in different germ layer precursors depending on the group, and does not play a broad role in endoderm and mesoderm specification in all groups. Especially intriguing are results in echinoderms, since nodal and Pitx are expressed in the ectoderm and endoderm (Duboc et al, 2010;Ohguro et al, 2011;Bessodes et al, 2012), and mesoderm cells are specified even when the pathway is blocked (Duboc et al, 2005). In addition, as mentioned above, asymmetric expression and the actions of the Nodal pathway are conserved features of deuterostomes.…”
Section: Introductionmentioning
confidence: 98%
“…However, there is relatively little evidence in vertebrates that Nodal signaling governs neural patterning during early development, although it is well known to be essential for specification of primary body axes and for formation of the mesoderm and endoderm (Shen, 2007). Vertebrate Nodal is expressed in the organizer, whereas ascidian and sea urchin Nodal genes are expressed in the ectoderm and endoderm (Bessodes et al, 2012;Chea et al, 2005;Morokuma et al, 2002). In amphioxus, Nodal is also expressed maternally in addition to the zygotical expression in the dorsal blastopore lip that is considered to be the equivalent of vertebrate organizer (Onai et al, 2010;Yu et al, 2007).…”
Section: Evolutionarily Conserved Roles Of Nodal and Bmps In Pns Formmentioning
confidence: 99%